Effects of Prepubertal Epididymal Ligation on the Androgen Receptor Distribution of the Rat Testis - Gur, Fatih Mehmet; Timurkaan, Sema (Sci Printers & Publ Inc, 2012)
OBJECTIVE: To investigate the effects of prepubertal epididymal obstruction on the androgen receptor (AR) distribution in the testis. STUDY DESIGN: Young rats were randomly divided into 2 groups for epididymal ligation and sham operation. In the ligation group the corpus epididymides were ligated bilaterally, while only laparatomy operation was performed in the sham group. Both groups were sacrificed at 21, 35, 56, 90 and 120 days. The testes were removed, fixed in Bouin's fixative and embedded in paraffin wax. The tissues were sectioned at 5 sum, stained with hematoxylin-eosin, and a microwave simulated antigen retrieval technique was used for immunohistochemistry. RESULTS: The first pathological alterations in the testes of ligated animals were observed at 56 days, and after that the alterations continued progressively. In 90 and 120 days of ligation the number of germ cells was reduced and seminiferous epithelium was mainly composed of Sertoli cells. AR immunostaining was detected in the nuclei of peritubular myoid cells, Sertoli cells, Leydig cells and pericytes but not in germ cells of the sham group rats. Except for the Sertoli cells, immunostaining properties of the ligation group rats were similar with those of the sham group. CONCLUSION: Progressive degenerative alterations occurred in the seminiferous tubules after prepubertal epididymal obstruction. The nuclei of Sertoli cells were not AR immunostaining in extensively degenerated seminiferous tubules. (Anal Quant Cytopathol Histopathol 2012;34:317-324)
Keywords: androgen receptor; epididymis; Sertoli cells; testis